ANALISIS KONDISI PENGELOLAAN SAMPAH BERKELANJUTAN DI TPA TEMESI GIANYAR - Reda Mata, Alfret Lango; Widiantara, I Kadek; Wahyu Wijaya, I Made (Jurnal Ecocentrism, 2026)
Sustainable waste management has become a highly strategic issue in Gianyar Regency, Bali, in line with the increasing volume of waste generation and the limited capacity of final disposal sites. This study aims to analyze the existing conditions and performance of waste management at the Temesi landfill based on technical, environmental, economic, and social aspects. The method employed is a descriptive-quantitative approach, involving field observations, interviews with site managers, documentation of operational data from January to May 2025, and mass balance analysis. The results indicate that the total waste generation reached 30,964 tons, with an average of 213.54 tons per day, predominantly composed of organic waste. Approximately 50.16% of the waste is processed into compost, 11.08% is recycled, and 38.76% remains as residual waste disposed of in the landfill. The material recovery rate has reached 61%, indicating that the system is moving toward the implementation of circular economy principles. Economically, the waste bank operation generates a surplus of IDR 149,933,210. However, environmental aspects remain a major challenge, particularly due to the suboptimal leachate treatment system, which poses a potential risk of environmental pollution. Furthermore, improvements in technological capacity and community participation are required to support more sustainable waste management.